Brock Biology of Microorganisms - Madigan, Michael T Martinko, John M (Pearson, 2015)
"This updated, 13th edition includes an evolutionary theme integrated throughout enables instructors to convey the modern view of evolution and gives students material that has been unified within a consistent and thematic context, making concepts easier to grasp. Units 1 and 2 are organized around foundational topics, providing an overview for the course and giving instructors flexibility to teach the later units in any order they wish. Unique coverage on Archael and Eukaryotic Molecular Biology (Chapter 7) gives instructors material they won't find anywhere else. Illustration and photo program gives students a clear and fascinating view into the microbial world. Illustrations and photos are often paired in a single figure to give students an idealized view next to a realistic view and to reinforce the connection between theory and practice. Microbial Sidebars, illustrated vignettes, present topical material related to a chapter's central theme. Several new sidebars that cover relevant and cutting-edge techniques including CRISPR Anti-Viral Defense System, Combinatorial Fluorescence Labeling, Bacterial Genomes, and Microbial Symbionts of Fungus-Cultivating Ants."--The Publisher.